Econometrics - Jeroen V. K. Rombouts; Luc Bauwens (Humboldt-Universität zu Berlin, Center for Applied Statistics and Economics (CASE), 2004)
Since the last decade we live in a digitalized world where many actions in human and economic life are monitored. This produces a continuous stream of new, rich and high quality data in the form of panels, repeated cross-sections and long time series . These data resources are available to many researchers at a low cost. This new erais fascinating for econometricians who can adress many open economic questions. To do so, new models are developed that call for elaborate estimation techniques. Fast personal computers play an integral part in making it possible to deal with this increased complexity.
Keywords: 330